Terahertz generation from surface of the bulk and monolayer tungsten diselenide - D. I. Khusyainov; A. V. Gorbatova; A. M. Buryakov (Российский технологический журнал)
The study of ultrafast laser interaction with graphene-like materials based on transition metal dichalcogenides attracts most scientific groups. It is connected with potential use of these materials in flexible optoelectronic devices of visible and THz range. In this paper the parameters of generation of terahertz field from the surface of bulk layered crystal and monolayer film of tungsten diselenide are analyzed. Generation of terahertz radiation from the surface of experimental samples was studied by the terahertz time-domain spectroscopy in reflection geometry. Bulk layered crystals of tungsten diselenide were grown by gas transport reactions. Monolayers of tungsten diselenide crystals were grown by chemical vapor deposition on a silicon substrate. The bandwidth of the generated terahertz radiation from the surface of the bulk layered tungsten diselenide crystal was ~ 3.5 THz. For tungsten diselenide monolayer the spectrum bandwidth of the generated THz radiation was ~ 2.5 THz. The peak amplitude of the generated terahertz field for both samples was at a frequency of ~ 1 THz. Research of the influence of the angle of rotation of a polarization plane of optical femtosecond pump on peak-to-peak amplitude of the generated terahertz field from the surface of investigated samples was carried out. Symmetry analysis of the azimuthal dependence of THz radiation made it possible to separate the mechanisms of THz radiation and evaluate their contribution. The analysis results confirm that the only possible contribution to the generation of terahertz radiation in a tungsten diselenide monolayer crystal is the second order nonlinear optical effect – optical rectification. One of the contributions to the generation of tungsten diselenide is a nonlinear-optical effect of the third order – surface optical rectification.